(untitled) (Eurasian Scientific Herald, 2023)
This article presents a scientific and theoretical analysis of the legal protection of personal data of founders, shareholders, investors, creditors , affiliates of joint-stock companies and other persons interested in joint-stock companies operating in Uzbekistan. Based on the results of the study, he put forward proposals for the protection of personal data for joint-stock companies within the framework of the national legislation of Uzbekistan.